Using Storytelling and Histories to Create Inclusive Spaces - Bunch, Marlee (Radical Teacher, 2023)
Teaching involves the responsibility of ensuring that learning spaces are both inclusive and equitable for all students, specifically marginalized groups. With the many issues that we as educators face in the current day, it is overwhelming at times to consider best practices to ensure that cultural competency and inclusion are actionable and apparent in the classroom. However, now more than ever, there is an urgency to begin actionable steps that move our schools and classrooms towards true inclusion with equitable practices. This suggests questions we can consider to help us recognize and act on this urgency: Are educators equipped with the necessary tools and support to implement lessons that mirror the growing diversity of students? What affects what they do? Are educators equipped with planning tools that also emphasize the importance and necessity of self-reflection as leaders in classrooms and learning spaces? Lastly, how can we use stories and histories to advance student knowledge and celebrate perspectives and inclusion? To address these questions I provide a four-dimensional framework which can be used to plan, analyze, and evaluate the content we present and implement in our classrooms. Such a framework allows a simplified, yet effective method of building and sustaining a truly inclusive and culturally minded learning space.